Synthesis of 2,4-Disubstituted-3,4-Dihydro-2H-Naphth[2,1-e][1,3]Oxazines - Turgut, Zuhal; Pelit, Emel; Turhan, Kadir (SPRINGER, 2009)
2,4-Disubstituted-3,4-dihydro-2H-naphth[2,1-e][1,3]oxazines were prepared through the ring-closure reactions of the starting aminonaphthols with substituted aromatic and hetaryl aldehydes.
Keywords: Aminonaphthol; biological activity; naphth-1,3-oxazines; ring-closure reactions; RING-CHAIN TAUTOMERISM; N-ALKYLATION; Biochemistry & Molecular Biology; Chemistry